Field Experiences in Breast Cancer Research among African American Women - Edwards, Beverly (Advances in Social Sciences Research Journal, 2017)
Despite many recent improvements in the health of Americans, substantial differences still exist among racial and ethnic groups. The frequently cited explanation for the disparity in health care for African Americans is lack of access to quality health care. Health care disparities are further complicated by increasing breast cancer rates of African American women without reduction of mortality rates. African American women have the highest breast cancer death rates. Despite all the gains that have been made in clinical, basic, and behavioral research, African American women continue to lag behind and remain disproportionately affected by this disease. In this qualitative pilot study, factors contributing to breast cancer risk in African American women were explored. Data was collected in four focus group sessions, where the study’s participants were asked questions related to their perceptions of health status, lifestyles, and health care access. Cultural values had a major impact relating to food preferences, food preparation and seeking health care. These participant narratives provide insight into issues regarding their breast cancer risks and suggestions for future research.